2010
DOI: 10.1038/nchembio.453
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule inhibition of Wnt signaling through activation of casein kinase 1α

Abstract: Wnt/β-catenin signaling is critically involved in metazoan development, stem cell maintenance and human disease. Using Xenopus laevis egg extract to screen for compounds that both stabilize Axin and promote β-catenin turnover, we identified an FDA-approved drug, pyrvinium, as a potent inhibitor of Wnt signaling (EC50 of ~10 nM). We show pyrvinium binds all casein kinase 1 (CK1) family members in vitro at low nanomolar concentrations and pyrvinium selectively potentiates casein kinase 1α (CK1α) kinase activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
447
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 436 publications
(472 citation statements)
references
References 49 publications
21
447
2
2
Order By: Relevance
“…To determine whether injury-induced β-catenin stabilization is necessary for retina regeneration, we stimulated β-catenin degradation in the injured retina of 1016 tuba1a:gfp fish by injecting eyes with pyrvinium, a casein kinase 1-α activator (24), or XAV939, a tankyrase inhibitor (25), along with a 3-h pulse of BrdU at 4 dpi. Pyrvinium and XAV939 dramatically reduced injury-dependent β-catenin accumulation, GFP transgene expression, and proliferation of MG-derived progenitors (Fig.…”
Section: Ascl1a-dependent Suppression Of Dkk Gene Expression In Injuredmentioning
confidence: 99%
“…To determine whether injury-induced β-catenin stabilization is necessary for retina regeneration, we stimulated β-catenin degradation in the injured retina of 1016 tuba1a:gfp fish by injecting eyes with pyrvinium, a casein kinase 1-α activator (24), or XAV939, a tankyrase inhibitor (25), along with a 3-h pulse of BrdU at 4 dpi. Pyrvinium and XAV939 dramatically reduced injury-dependent β-catenin accumulation, GFP transgene expression, and proliferation of MG-derived progenitors (Fig.…”
Section: Ascl1a-dependent Suppression Of Dkk Gene Expression In Injuredmentioning
confidence: 99%
“…Blocking of CK1α function with D4476, (4[4-(2,3-dihydro-benzo [1,4]-dioxin-6-yl)-5-pyridin-2-yl-1-H-imidazol-2-yl]benzamidine) which is an ATP-competitive inhibitor, had the same results with the morpholino injection, such as expression of CK1a was decreased; chromosome congression failed; oocytes arrested at pro-MI phase; PB1 extrusion failed or extruded giant PB1; the ability of embryo development was impaired. However, mouse oocytes treated with pyrvinium pamoate (PP), which increased phosphorylation and allosteric activation of CK1α [47], induced oocyte meiotic maturation failure, severe congression abnormalities and misalignment of chromosomes. These results indicated that CK1α affect homologous chromosome alignment, congression and segregation in the oocyte meiosis and play an important role in early embryo development.…”
Section: The Role Of Ck1 Isoforms In Meiosismentioning
confidence: 99%
“…Meanwhile, CK1α also participated in the same pathway and allosteric activation of CK1α as an effective mechanism to inhibit Wnt signaling. Wnt signaling increases cytoplasmic levels of β-catenin, which enters the nucleus and interacts with other factors to activate a β-catenin-Tcf/Lef-mediated transcriptional program [47]. But high expression of β-catenin induced abnormal chromosome separation.…”
Section: The Role Of Ck1 Isoforms In Meiosismentioning
confidence: 99%
“…Whether the underlying mechanisms of activation are similar remains to be determined. The C-terminal regulatory domain of CK1δ blocks pyrvinium action [11], whereas DDX3 is able to activate full-length CK1δ. Pyrvinium and DDX3 might interact with the same region on CK1, but the protein activators may function more efficiently than small molecules.…”
Section: Unwinding the Wnt Action Of Casein Kinasementioning
confidence: 99%
“…While allostery has a proud history in enzymology, there are only a few examples (e.g., AMP-kinase, phosphorylase kinase) of small-molecule allosteric regulation of protein kinases [reviewed in 10]. Notably, a recent screen for inhibitors of the Wnt/β-catenin pathway identified the drug pyrvinium pamoate as an allosteric activator of CK1α [11]. As a clue to mechanism, pyrvinium bound to but did not activate other CK1 isoforms.…”
mentioning
confidence: 99%